Strategi Komunikasi Kepala Sekolah dalam Meningkatkan Motivasi Kinerja Guru di MIS Nurul Iman Kecamatan Gebang - Fadilah Istighfara; Ahmad Zaki (Lembaga Riset Ilmiah, 2022)
The problem in the research shows that principals face obstacles such as the use of school operational funds that have not been fully utilized to provide rewards in motivating teacher performance and welfare. The weak figure of the principal who is a woman and has to lead some male teachers. So it is feared in carrying out their duties and functions as a leader. The purpose of the study was to determine the leadership strategy in increasing the motivation of teacher performance at MIS Nurul Iman Gebang. The type of research used is qualitative research. Methods of collecting data by means of observation, interviews and documentation. Data validity test techniques include data credibility test (internal validity), data dependability (reliability) test, transferability test (external validity/generalization), and confirmability test (objectivity). The results of this study are that there is a leadership role used by the head of MIS, Nurul Iman Gebang, even though a woman does not affect the effectiveness of leadership in managing education. The leadership model applied is a persuasive approach, namely MIS head Nurul Iman Gebang leads with more familiar techniques and guides teachers in improving teaching performance through concrete examples and increasing motivation to pursue educators in order to maintain integrity, solidity and solidarity.